2021
DOI: 10.1038/s41598-021-00973-5
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Plasmodium falciparum infections enhance transmission-reducing immunity development

Abstract: Subclinical infections that serve as reservoir populations to drive transmission remain a hurdle to malaria control. Data on infection dynamics in a geographical area is required to strategically design and implement malaria interventions. In a longitudinal cohort, we monitored Plasmodium falciparum infection prevalence and persistence, and anti-parasite immunity to gametocyte and asexual antigens for 10 weeks. Of the 100 participants, only 11 were never infected, whilst 16 had persistent infections detected b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“… 20 , 54 Importantly, the humoral response to gametocyte TBV immunogens such as Pfs230 may be reinforced by prior and/or subsequent natural infection. 55 Humoral responses against Pfs230 are common in malaria endemic regions, 56 , 57 and we have recently shown that affinity-purified Pfs230-specific antibodies can indeed block transmission. 21 LMIV230-01 is the only other human-derived mAb reported to date with observed TRA 18 ( Figure 5 C) and is encoded by IGHV1-69 and IGKV1-5 , which were the most common germline genes identified from the memory B cells sequences obtained from the eight vaccinees in Coelho et al.…”
Section: Discussionmentioning
confidence: 99%
“… 20 , 54 Importantly, the humoral response to gametocyte TBV immunogens such as Pfs230 may be reinforced by prior and/or subsequent natural infection. 55 Humoral responses against Pfs230 are common in malaria endemic regions, 56 , 57 and we have recently shown that affinity-purified Pfs230-specific antibodies can indeed block transmission. 21 LMIV230-01 is the only other human-derived mAb reported to date with observed TRA 18 ( Figure 5 C) and is encoded by IGHV1-69 and IGKV1-5 , which were the most common germline genes identified from the memory B cells sequences obtained from the eight vaccinees in Coelho et al.…”
Section: Discussionmentioning
confidence: 99%
“…The MOI is an important parameter for the evaluation of level of malaria transmission and human immunity in a given locality [ 23 ]. In this study, the multiple infection rate and mean of MOI varied between study sites and were higher in rural areas than in urban areas.…”
Section: Discussionmentioning
confidence: 99%
“…Specific antibodies against sexual-stage antigens are also related to age and serve as markers of exposure, increasing according to gametocyte densities [ 62 , 74 , 75 ], but no correlation with epidemiological parameters was found in this study. This finding is not surprising since, in malaria-endemic areas, infections are determined by microscopic parasite counts, and gametocytes normally occur at low densities.…”
Section: Discussionmentioning
confidence: 54%